KONSEP STRATEGI MARKETING LEMBAGA PENDIDIKAN ISLAM - Hobir, Abdul; Fauzan, Fauzan (Journal of Education Partner, 2024)
The concept of marketing strategies that Islamic educational institutions can apply to increase visibility, attractiveness, and success in attracting the interest of prospective students. Marketing strategies in this context include the use of social media such as Facebook, Instagram, and LinkedIn to expand their reach, interact with potential audiences, and build a strong and recognizable brand, educational content marketing for example, content about the excellence of Islamic education, student achievement, or interesting extracurricular activities, and a community approach through collaboration with local and global communities, Islamic educational institutions can build strong relationships and expand their networks. The study also evaluates the challenges faced by Islamic educational institutions in implementing modern marketing strategies and provides suggestions for overcoming these obstacles.